Potensi dan Mekanisme Kacang Tropis terhadap Sindrom Metabolik: Tinjauan Literatur: The Potential Benefits and Mechanism of Action of Tropical Nuts Against Metabolic Syndrome: A Literature Review - Setyawati, Amalia Rani; Anjani, Gemala; Mahati, Endang (Universitas Airlangga, 2024)
Background: Metabolic syndrome is a significant risk factor for both type 2 diabetes mellitus and cardiovascular disease, with a high prevalence in Asia Pacific, particularly in Indonesia. To reduce its prevalence, several studies have recommended the use of tropical nuts, which can be developed as functional foods and complementary treatment. In this context, the bioactivities of tropical nuts can largely be attributed to their rich content of monounsaturated fatty acids, polyunsaturated fatty acids, fiber, minerals, vitamins, phytosterols, and polyphenols. Objectives: This literature review aims to evaluate the potential benefits and mechanism of action of tropical nuts against metabolic syndrome. Methods: The study design was a literature review of several articles from 3 online databases, including PubMed, Google Scholar, and ScienceDirect. Discussions: The results showed that tropical nuts (peanut, sacha inchi, cashew, tropical almond, and Brazil nut) had several biologically active components, such as arginine, fiber, fatty acid, mineral, vitamin, phenolic compounds, resveratrol, and phytosterol. The test samples were reported to have the ability to modulate Nrf2, SOD, MDA, GSH, GPx, and CAT due to their antioxidant activity. In inflammation, tropical nuts had a significant effect on NF-κB, NLRP3, TNF-ɑ, IL-8, IL-1ꞵ, IL-6, and IL-10. The results also showed their ability to enhance lipid synthesis, nitric oxide production, advanced glycation end-product, prostaglandin, SIRT3, homocysteine, protein kinase C, adhesion molecules, platelet aggregation, GLP-1, PYY, AGRP, PPARɑ/ꞵ/δ, GLUT4, and insulin receptor. Conclusions: Tropical nuts had beneficial effects on metabolic syndrome due to their bioactivities, including antioxidants, anti-inflammatory, anti-obesity, antidiabetic, antihypertensive, anti-dyslipidemia, and cardioprotective.